WORKING WITH UNSUCCESSFUL STUDENTS IN ENGLISH LESSONS - Bektursinova Sarbinaz Davletovna (Journal of new century innovations, 2022)
The growing number of underachieving and poorly performing students is one of the main problems of the modern school. Recently, psychologists and educators, together with doctors, have noted a steady increase in the number of children with problems in general behavior and learning. The actual problem of our school is “not to lose”, “not to miss” students with low educational opportunities. Its solution involves the improvement of methods and forms of organization of education, the search for new, more effective ways of forming knowledge among students that would take into account their real capabilities.